Jane's military vehicles and logistics 2010-2011 - Connors, Shaun C; Foss, Christopher F. (IHS Global Limited, an imprint of Jane's Information Group Inc., 2010)
Presents the data you need on the advances in communications and IT systems and equipment designed for, and fielded by, armed forces around the world. This title contains descriptions of each system's development programme; its operating parameters; how it works in battlefield conditions; and, its capacity to integrate with other systems